The Oxford Companion to American Theatre - Bordman, Gerald Martin; Hischak, Thomas S.; Oxford University Press ([New York, N.Y.] ; [Oxford] : Oxford University Press, 2004)
A guide to the American stage from its beginnings to the present. Includes entries on playwrights, plays, actors, directors, producers, songwriters, famous playhouses, dramatic movements, classic works, commercially successful plays, and foreign figures that have influenced American dramatic development.
""Foreword""; ""Preface to the Third Edition""; ""From the Preface to the First Edition""; ""The Oxford Companion to American Theatre""; ""A""; ""B""; ""C""; ""D""; ""E""; ""F""; ""G""; ""H""; ""I""; ""J""; ""K""; ""L""; ""M""; ""N""; ""O""; ""P""; ""Q""; ""R""; ""S""; ""T""; ""U""; ""V""; ""W""; ""Y""; ""Z""
Title from home page (Oxford University Press, viewed Oct. 11, 2005).
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
eBooks on EBSCOhost
Keywords: Drama; Fürstliches Schauspielhaus; Universidad Sergio Arboleda; Theater -- United States -- Dictionaries; Theater -- United States -- Biography -- Dictionaries; American drama -- Dictionaries; Theater -- United States; Drama; Théâtre -- États-Unis.; Théâtre (Genre littéraire); Théâtre -- États-Unis -- Biographies -- Dictionnaires anglais; plays (performing arts compositions); drama (literary genre); PERFORMING ARTS -- Theater -- History & Criticism; Drama; American drama; Theater; United States; Dramatiker; Schauspieler; USA; Theater; Toneel; Théâtre (Spectacle); Théâtre américain (Littérature); Comédien.; États-Unis.; theater; theatre; uitvoerende kunsten; performing arts; drama; uitvoerend kunstenaars; performers; naslagwerken; reference works; vs; usa; Arts (General); Kunst (algemeen); dictionaries; collective biographies; Biographies; Dictionaries; Dictionaries; Biographies; Répertoire (Descripteur de forme); Dictionnaire (Descripteur de forme); Dictionaries; Biographies; Dictionnaires; Biographies